2020
DOI: 10.1128/jvi.01560-20
|View full text |Cite
|
Sign up to set email alerts
|

Orsay Virus CP-δ Adopts a Novel β-Bracelet Structural Fold and Incorporates into Virions as a Head Fiber

Abstract: Fiber proteins are commonly found in eukaryotic and prokaryotic viruses where they play important roles in mediating viral attachment and host cell entry. They typically form trimeric structures and are incorporated into virions via non-covalent interactions. The small RNA virus Orsay, which specifically infects the laboratory model Caenorhabditis elegans, encodes a fibrous protein δ that can be expressed as a free protein and as a capsid protein-δ (CP-δ) fusion protein. Free δ has previously been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…OrV has a positive-sense, bi- segmented RNA genome of ∼6.3 kb which encodes four proteins: an RNA-dependent RNA polymerase (RdRP), a viral capsid protein (CP), protein (8), and a protein fusion of CP-8 (Félix et al, 2011; Jiang et al, 2014). Free 8 mediates nonlytic viral release (Yuan et al, 2018) and the CP-8 fusion is incorporated into the virions as pentameric head fibers (Fan et al, 2017; Guo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…OrV has a positive-sense, bi- segmented RNA genome of ∼6.3 kb which encodes four proteins: an RNA-dependent RNA polymerase (RdRP), a viral capsid protein (CP), protein (8), and a protein fusion of CP-8 (Félix et al, 2011; Jiang et al, 2014). Free 8 mediates nonlytic viral release (Yuan et al, 2018) and the CP-8 fusion is incorporated into the virions as pentameric head fibers (Fan et al, 2017; Guo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In RNA2, we found a hotspot in the first 20 nucleotides, and two others between nucleotides 400-500, within the S domain of the CP (Guo et al, 2014), and 1500-1600, from the end of the second alpha sheet to beta sheet 6 of the 8 protein (Fig. 4A, B) (Guo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The other common SNV (RNA 1: 302G>A) was not above the threshold in sample JUv1580_vlc RL2. (B) High variability hotspots (magenta) represented on the predicted structure of RdRp and PDB structures 4NWV and 5W82 of the CP trimer and 8 pentamer (amino acids 1-110), respectively (Guo et al, 2014, Guo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the free δ and the CP-δ fusion protein play different roles during viral exit and viral entry, respectively. While free δ was found to colocalize with terminal web and mediate nonlytic viral release (6), CP-δ is incorporated into infectious viral particles as a pentameric head fiber (7). The CP-δ head fiber adopts a novel bracelet structure with a terminal globular domain that is likely involved in host receptor engagement.…”
Section: Introductionmentioning
confidence: 99%